1999
DOI: 10.1021/ac980890p
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ginsenosides in Plant Extracts from Panax ginseng and Panax quinquefolius L. by LC/MS/MS

Abstract: An HPLC/MS/MS method has been developed for the characterization and quantification of ginsenosides contained in extracts of the root of Panax ginseng (Korean ginsengs) and Panax quinquefolius L. (American ginsengs). The [M + H]+ and [M + Na]+ ions were observed for ginsenoside standards (Rb1, Rb2, Rc, Rd, Re, Rf, Rg1) and four different ginseng extracts. The glycosidic linkages, the core, and the attached sugar(s) of the ginsenosides can be determined from the collision-induced dissociation spectra from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
163
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 11 publications
8
163
0
Order By: Relevance
“…The composition of both the present and our original batch is consistent with panax quinquefolius L. Key ratios and the presence and absence of various ginsenosides are used in the authentication of ginseng. A ratio of Rb 1 :Rg 1 > 3 (Ma et al, 1996;Awang et al, 2000) and ratios of Rg 1 :Re and Rb 2 :Rc < 1 have been shown to be indicative of Panax quinquefolius L. (Chan et al, 2000;Wang et al, 1999). The most powerful marker is the absence of Rf, a ginsenoside not found in AG and distinctive for Asian ginseng (Ma et al, 1996;Awang et al, 2000;Chan et al, 2000;Li et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The composition of both the present and our original batch is consistent with panax quinquefolius L. Key ratios and the presence and absence of various ginsenosides are used in the authentication of ginseng. A ratio of Rb 1 :Rg 1 > 3 (Ma et al, 1996;Awang et al, 2000) and ratios of Rg 1 :Re and Rb 2 :Rc < 1 have been shown to be indicative of Panax quinquefolius L. (Chan et al, 2000;Wang et al, 1999). The most powerful marker is the absence of Rf, a ginsenoside not found in AG and distinctive for Asian ginseng (Ma et al, 1996;Awang et al, 2000;Chan et al, 2000;Li et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, NAG contains a 3-to 5-times higher content of ginsenosides and different profile of ginsenosides than both forms of P ginseng. 2,15,16,24,28 As well, KRG is the only marketed ginseng to contain ginsenoside Rg 3 , the most potent vasodilating ginsenoside. 36 To date, 4 clinical interventions have tested the effect of P ginseng root on BP.…”
Section: Discussionmentioning
confidence: 99%
“…15 Briefly, the total ginsenoside content of NAG was 62.8 mg/g; as well, its authenticity was indicated by the lack of ginsenoside Rf, which is absent from NAG but found in other ginseng species, such as P ginseng. 24 We administered NAG and cornstarch as powders in identical blue-white 500 mg #00 capsules (with vanilla extract added to mask smell and taste), which were prepared by Sunny Crunch Foods Ltd (Markham, Ontario, Canada).…”
Section: Treatments and Protocolmentioning
confidence: 99%
“…Third, the batches had a typical NAG ginsenoside profile, lacking ginsenoside Rf and containing a low PPT/PPD ginsenoside ratio. 14,[17][18][19] The findings of this study are significant in light of the form and dose of NAG used, as well as the study design used. We used whole dried root, which is the primary, or natural, form of NAG that cultivators sell to marketers and manufacturers.…”
Section: Discussionmentioning
confidence: 99%